Penerapan Prinsip Customer Due Diligence dalam Pencegahan Tindak Pidana Pencucian Uang : (Studi Kasus Pada Bank: BRI, BNI, BCA, DANAMON) - Bunga Ichwanda Solikha; Anas Firman Adi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The principle of Customer Due Diligence (CDD) is an important preventive measure in preventing money laundering in the banking sector. This research aims to analyze the implementation of the CDD principle at BRI, BNI, BCA, and Danamon, including customer identification, transaction monitoring, and reporting suspicious transactions as part of compliance with anti-money laundering regulations. This study uses a qualitative approach with a literature study method. The results indicate that the effectiveness of CDD implementation varies, influenced by internal factors such as technology and training, as well as external factors such as supervisory authority. The implementation of Customer Due Diligence (CDD) by the four banks has proven to contribute to the prevention of money laundering, although improvements in operations and regular evaluations are needed. This research recommends enhancing the automated monitoring system, ongoing staff training, and stronger coordination with the Financial Transactions Reports and Analysis Center (PPATK) and the Financial Services Authority (OJK) to strengthen compliance and the effectiveness of CDD.